The antibacterial effect of Ellagic acid on Lacto bacillus acidophilus in comparison to Chlorhexidin (Mustansiria Dental Journal, 2019)
Ellagic acid is a natural herb extract were prepared from flesh pomegranate extract. The preparation and experiments were done and conducted in a laboratory of chemistry department of Ministry of Science and Technology. Biological activity of Ellagic acid to ward pathogenic bacteria (Lactobacillus acidophilus) was studied. The purpose of this study was to evaluate the antibacterial effect of prepared Ellagic acid with different concentrations on growth of lacto bacillus acidophilus in comparison with Chlorhexidine gluconate 0.2% and deionized water. This in vitro bacteriological study was tested according to agar well diffusion technique. The results showed that a highly significant increase in mean values of Ellagic acid compared to Chlorhexidine and deionized water. The concentration, 5 mg/ml and10 mg/ml of Ellagic acid showed stronger effects in inhibition of lactobacillus acidophilus, than Chlorhexidine 0.2%. Ellagic acid 5and10mg/ml has the ability to interfere   with the adherence of Lactobacilli in vitro.  Previous  study showed that Ellagic acid had antibacterial effect  on Streptococcus mutans ,  Ellagic  acid could be  used  as antibacterial  mouth washes   to prevent dental caries. Chlorhexidine.